Smoking Enigma in Coronavirus Disease 2019: A Tug of War between Predisposition and Possible Way Out. (March 2021) - Rakhi, Nadira Naznin; Biswas, Ritu
Background: The recent global inclination for smoking during the Coronavirus Disease 2019 (COVID-19) pandemic has drawn attention to the impact of smoking on COVID-19. While smoking increases susceptibility to common respiratory pathogens including the closely related coronaviruses, COVID-19 causing Severe Acute Respiratory Coronavirus 2 (SARS-CoV-2) being a respiratory pathogen intrigues the possible association between smoking and viral pathogenicity. Smoking and COVID-19: The gender dependence of COVID-19 infection rates and a higher prevalence of smokers among males made the scientific world assume smoking to be a confounding variable in sex predisposition to COVID-19. Conversely, the controversial findings of discrepant morbidity and mortality rates of COVID-19 among smokers questioned the credibility of this hypothesis. More importantly, nicotine in smoking has been hypothesized to downregulate Interleukin-6 (IL-6) which plays a role in COVID-19 severity and to interfere with the Angiotensin-Converting Enzyme 2 (ACE2), the receptor of SARS-CoV-2 led the scientists to experiment nicotine patch prophylactically against COVID-19. Besides, interaction between spike protein and nicotinic acetylcholine receptors (nAChRs) supports the nicotinic cholinergic system dysregulation hypothesis in COVID-19 pathophysiology leading to its therapeutic use. However, despite the contradictions in the direct impact of smoking, it surely acts as fomites for viral transmission. Conclusion: Irrespective of the role nicotine in COVID-management, compassionate use of smoking against SARS-CoV-2 cannot be recommended until the therapeutic value gets proved and therapeutic form becomes available.